Mechanisms of initiation and reversal of drug-seeking behavior induced by prenatal exposure to glucocorticoids - Rodrigues, Ana João (2012)
We would like to thank the members of the Neuroscience Research Domain at ICVS for all the helpful discussions and suggestions. We are especially thankful to the animal facility caretakers, and to Drs Sara Silva, António Melo and Ana Paula Silva and Dieter Fischer for their help